2009
DOI: 10.1159/000191103
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Proanthocyanidins Ameliorate Diabetic Nephropathy via Modulation of Levels of AGE, RAGE and CTGF

Abstract: Background: Diabetic nephropathy (DN) is the most common cause of end-stage renal failure. Grape seed proanthocyanidin extracts (GSPE) are powerful antioxidants. However, the role of GSPE on advanced glycation end products (AGEs), receptor for advanced glycation end products (RAGE) and expression of connective tissue growth factor (CTGF) in DN has not been elucidated. Using streptozotocin-induced diabetic rats, we evaluated the effects of GSPE in DN. Methods: Wistar rats were induced into diabetes using strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 59 publications
8
28
0
Order By: Relevance
“…Immunofluorescence results showed that RAGE directly binds with TXNIP, indicating that related regulatory triggering occurs among ROS, RAGE, and TXNIP. PSPC effectively eliminated the obesity that was induced by administration of a HFD and treatment efficacy was achieved based on attenuation of oxidative stress and dampening of the RAGE/TXNIP signaling pathway, similar to recent reports (16,25).…”
Section: Resultssupporting
confidence: 83%
“…Immunofluorescence results showed that RAGE directly binds with TXNIP, indicating that related regulatory triggering occurs among ROS, RAGE, and TXNIP. PSPC effectively eliminated the obesity that was induced by administration of a HFD and treatment efficacy was achieved based on attenuation of oxidative stress and dampening of the RAGE/TXNIP signaling pathway, similar to recent reports (16,25).…”
Section: Resultssupporting
confidence: 83%
“…The superoxide anion scavenging activity of GSPE was stronger than vitamin C, vitamin E or any other antioxidant. 1) It has been reported to have protective effects on various cardiac disorders, correct dyslipidemia associated with high-fat diet, 2) decrease arterial pressure in estrogen-depleted female spontaneously hypertensive rats, 3) prevent diabetic nephropathy and neuropathy from progressing, 4,5) and most importantly, ameliorate atherosclerosis, 6) possibly attributed to its endothelial protective potential.…”
mentioning
confidence: 99%
“…For in vitro studies, there are many DN models commonly used in TCM edible plants, such as mouse embryonic fibroblastadipose like cells (3T3-L1), L6 myotubes, human mesangial cells, mouse mesangial cells (MES-13), mouse podocyte cells, murine skeletal myoblasts (C2C12), murine hepatocytes (H4IIE), renal proximal tubular epithelial cells (HK-2), rat insulinoma cells (INS-1), glomerular endothelial cells, and vascular endothelial cells (Eid et al, 2010;Lee et al, 2010;Li et al, 2009Li et al, , 2010 Yu, Gao, & Liu, 2010;Zhang, Liu, Xiong, Gong, & Tan, 2012). All these in vivo and in vitro models enhance our understanding of the mechanisms of the protective effects of TCM edible plants against DN.…”
Section: Experimental Dn Models Used In Tcm Edible Plants Studymentioning
confidence: 99%
“…Experimental studies also demonstrated the nephro-protective effect of ginger in STZ-induced diabetic rat via regulating intra-and extra-mitochondrial enzymes (Ramudu et al, 2011). Strikingly, grape seed proanthocyanidins showed a pronounced therapeutic effect on experimental DN through multiple cellular targets (Cheng et al, 2007;Li et al, 2009;Liu, Shen, & Yao, 2006;Mansouri et al, 2011). Furthermore, the formation of AGEs was inhibited in db/ db mice after treatment with Pu-erh tea (Yan et al, 2012).…”
Section: Bioactive Components From Tcm Edible Plantsmentioning
confidence: 99%
See 1 more Smart Citation